Bias Gender on Language Learning: An Exploration on Gender Based Ability of Learning English as Foreign Language of The Secondary School Students - mutohar lutfi; Adinda Cahayani Supriyanto; Aqiel Sifa` Abdallah Putra; Fitri Rakhmawati (The Journal Of English Teaching For Young And Adult Learners, 2023)
The diversity in the process of learning language is wonderful, especially the diversity between males and female student on their understanding in learning English as foreign language which is relate to their language learning competence. In this case the language learning abilities are biased by gender which affected their learning output. Hypothetically, there must be relations between the gender identity and learning ability toward English learning output. To verify the hypothesis, the authors begin with the formulation of collective data collection that collected from the student`s English written text products from the secondary school which targeted high school students, then the data will be analyzed with systemic functional linguistics and feminist stylistics approach to understand the gender bias on the texts construction and to investigating the structural choice of language. The data analysis also elaborates with language learning theory to support the evidence and to verify the hypothesis. This research is designed for the development of language learning especially in English as foreign language. The development is addressed the future researchers and language teachers to develop the theory and to arrange the language learning strategies for better future of language education.